Dynamic covalent network-enabled poly (vinyl alcohol)/carboxymethyl cellulose films: A self-reinforcing and recyclable approach for sustainable fruit packaging - Liu, Fengsong; Wang, Zihan; Cao, Yifang; Tan, Tai Boon; Fan, Yiting; Ren, Jiahao; Zou, Youning; Chen, Ying; Xie, Yijia; Xiao, Xinglong (Elsevier B.V., 2025)
Developing sustainable packaging materials with enhanced mechanical strength and moisture resistance remains a pressing challenge. In this study, a self-reinforcing and recyclable film composed of poly (vinyl alcohol) (PVA) and carboxymethyl cellulose (CMC) was fabricated through dynamic covalent crosslinking. The strategy involved the formation of amide bonds (-CONH-) between the -COOH groups of CMC and the -NH2 groups of N-isopropylacrylamide (NIPA), thereby reinforcing intermolecular entanglements and enhancing structural integrity. Comprehensive characterization using X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) confirmed the construction of a robust double-crosslinked network. This architecture substantially reduced water absorption and improved film durability. The optimized PVA-10 % N-CMC film exhibited enhanced hydrophobicity, as evidenced by a water contact angle of 97.36°, low water solubility (14.67 %), and minimal water vapor permeability (0.88 g × mm/m2 × h × kPa). Moreover, its outstanding mechanical performance and recyclability under varying humidity conditions underscore its potential as an eco-friendly packaging material. Notably, the film effectively prolonged the freshness of strawberries, maintaining fruit quality for up to 9 days during storage. Collectively, these findings offer a scalable approach for engineering high-performance biodegradable films, paving the way for advanced smart food packaging technologies.